Which former professional football players become successful professional head coaches? - Matteo Balliauw; Marco Verheuge; Stijn Baert (Global Labor Organization (GLO), 2022)
One of the potential avenues for former professional football players to pursue their career is to become a head coach of a club's first team. An important question is how to best prepare for such a reconversion. This letter is the first in the academic literature quantifying the association between success as a professional head coach and prior experience of former professional players as a youth coach, player-coach, head coach at a lower division, assistant coach, in other staff positions and in club management positions. Our regression analyses, based on unique coach career data, show a significant positive association for the jobs of assistant or youth coach.
Keywords: L83; Z22; Z2; 330; football; coaching; education; regression analysis; sports management